Renal Thrombotic Microangiopathy Associated with the Use of Bortezomib in a Patient with Multiple Myeloma - Jan Van Keer; Michel Delforge; Daan Dierickx; Kathelijne Peerlinck; Evelyne Lerut; Ben Sprangers (Case Reports in Hematology)
Bortezomib is a first-generation proteasome inhibitor used in the treatment of multiple myeloma (MM). A few reports have linked bortezomib exposure with the development of thrombotic microangiopathy (TMA). We describe a case of biopsy-proven renal thrombotic microangiopathy associated with the use of bortezomib in a 51-year-old man with IgG lambda MM. To our knowledge, this is the first biopsy-proven case. In addition, reexposure to bortezomib 18 months later was associated with recurrence of TMA. This supports a possible causal role of bortezomib. The exact mechanisms remain to be elucidated.